Growth responses of native chicken Sentul G-3 on diet containing high rice-bran supplemented with phytase enzyme and ZnO - Hidayat, Cecep; ., Sumiati .; Iskandar, Sofjan (Indonesian Animal Sciences Society, 2014)
This study was conducted to determine the effect of phytase enzymes and ZnO supplementation on the performance of native chicken Sentul-G3 fed high rice-bran diet. Two hundred and seventy day old chicks (DOC) native chicken Sentul-G3 from three different hatcheries were used in this study. Factorial randomized block design (3 x 3) was applied in this study. The first factor was the enzyme phytase supplementation levels (0; 1000; 2000 U/kg), the second factor was the level of supplementation of ZnO (0; 1.5; 3.2 g/kg), so that there are nine treatment given, namely R1 = 50% commercial diet : 50% rice bran; R2 = R1 + 1.5 g ZnO/kg; R3 = R1 + 3.2 g ZnO/kg; R4 = R1 + phytase enzyme 1000 U/kg; R5 = R1 + (phytase enzyme 1000 U/kg + 1.5 g ZnO/kg); R6 = R1 + (phytase enzyme 1000 U/kg + 3.2 g ZnO/kg); R7 = R1 + phytase enzyme 2000 U/kg; R8 = R1 + (phytase enzyme 2000 U/kg + 1.5 g ZnO/kg); R9 = R1 + (phytase enzyme 2000 U/kg + 3.2 g ZnO/kg). Each experimental unit consisted of 6 head unsexed native chicken Sentul-G3. The experimental diet was fed for 10 weeks. The variables measured were body weight, body weight gain, feed intake, feed conversion ratio, mortality, mineral deposition of Ca, P, Zn in the tibia bone, alkaline phosfatase enzyme activity in serum. Results showed that there was significant interaction (P<0.05) between phytase enzyme and ZnO supplementation on body weight, body weight gain, feed conversion, zinc deposition in the tibia bone. There was no significant interaction (P> 0.05) between phytase enzyme and ZnO supplementation on feed intake, mortality, alkaline phosphatase enzyme activity in serum, and deposition of calcium and Â phosphorus in the tibia bone. It was concluded that supplementation of phytase enzyme and ZnO were not able to increase the growth of native chicken Sentul-G3 on fed diet containing high rice bran. Key Words: Phytase Enzymes, ZnO, Native Chicken Sentul-G3